2019
DOI: 10.1039/c9ta05608d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the high-voltage Mg2+/Na+ co-intercalation reaction of Na3VCr(PO4)3 in Mg-ion batteries

Abstract: A Na3VCr(PO4)3 cathode facilitates a high voltage Mg2+/Na+ co-intercalation reaction entailing V3+/V4+ and V4+/V5+ redox couples at 1.7–2.3 V vs. Mg2+/Mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…In the other three analogues, two distinct couples of redox reaction peaks at ≈3.65/3.25 and ≈4.1/3.9 V were observed, corresponding to the reversible transition of V 3+ / 4+ and V 4+ / 5+ , respectively. The substitution of V 3+ by Cr 3+ in Na 3 V 2 (PO 4 ) 3 activates the redox reaction of V 4+ /V 5+ to boost the energy density, in accord with previous studies …”
Section: Resultssupporting
confidence: 90%
“…In the other three analogues, two distinct couples of redox reaction peaks at ≈3.65/3.25 and ≈4.1/3.9 V were observed, corresponding to the reversible transition of V 3+ / 4+ and V 4+ / 5+ , respectively. The substitution of V 3+ by Cr 3+ in Na 3 V 2 (PO 4 ) 3 activates the redox reaction of V 4+ /V 5+ to boost the energy density, in accord with previous studies …”
Section: Resultssupporting
confidence: 90%
“…Sodium-ion batteries (SIBs) are among the most promising energy-storage systems because of the low cost and abundance of Na. Despite the great improvement in battery performance at high/room temperature, rapidly reduced energy/power outputs and cycle stability at subzero temperature (subzero-T) highly limit their application in colder climates. , The decreased ionic conductivity of the electrolyte, sluggish solid ion diffusion in the electrodes, and increased interface impedance between electrodes and electrolytes all result in a deterioration in battery performance at low temperatures. Great efforts have been made to develop new electrolytes for subzero-T conditions, leading to the conclusion that a mixture of EC and PC is the best solvent formulation for Na/hard carbon cells. , Moreover, both 1.0 M NaClO 4 dissolved in EC+PC+FEC and 1.0 M NaCF 3 SO 3 dissolved in diglyme have high ionic conductivity at −30 °C. , Recent studies have found that cathode materials may not be the main limitation for subzero-T Li-ion storage performance, with LiCoO 2 retaining nearly 72% of its room-temperature capacity at −40 °C. , This phenomenon has also been demonstrated in the NASICON-type electrode in Na-ion and Mg-ion batteries; both Na 3 V 2 (PO 4 ) 3 and Na 3 Ti 2 (PO 4 ) 3 have attractive low-temperature adaptability in SIBs, whereas Na 3 VCr­(PO 4 ) 3 cathode exhibits better reversibility and fewer phase changes at −15 °C than that at 30 °C in Na-ion and Mg-ion systems. Besides, modification strategies including increasing the electrochemically active surface area by morphological regulation, surface doping, and modifying the electrolyte/electrode interface through electrolyte additives can effectively enhance the subzero-T performance of SIBs cathodes. However, less attention has been paid to anode materials for SIBs, most of which are carbon materials. Moreover, there is a lack of systematic research and quantitative analysis regarding transfer dynamics and ion diffusion kinetics of anode materials at low-temperatures.…”
mentioning
confidence: 99%
“…Apart from the TMDs, NASICON-type cathodes attract much attention as insertion electrode materials due to the structural stability as well as fast ion conduction. They are described as a rigid framework with interconnected vacant sites which allow the insertion of alkali ions, including Na 3 V 2 (PO 4 ) 3 , [154,155] NaTi 2 (PO 4 ) 3 , [156] Na 2 VTi(PO 4 ) 3 , [149] NaV 6 O 15 , [157][158][159] Na 3 VC r(PO 4 ) 3 , [160] Na 5 V(PO 4 ) 2 F 2 , [161] and so on. As a result, they are also naturally used as cathodes for MNHIBs.…”
Section: Mg 2+ /Na + Hybrid Ion Batteriesmentioning
confidence: 99%